Slovenian Public Libraries in 2010 - Gorazd Vodeb (Knjižnica, 2012)
ABSTRACT Purpose:  The article presents the 2010 Slovenian public library statistics. Performance indicators are compared to library regulations and standards, and to the goals of the Resolution on the 2008-2011 National Programme for Culture. Opening time, library space and equipment, the size of collections and the number of additions are surveyed. Staff structure and financial data are presented as well as the data about visitors, registered members, loans and other library services. Methodology/approach:  Data collected via the annual statistical survey of Slovenian public libraries are used. They were collected and published by the Library System Development Centre at the National & University Library. Results:  Data show the stability of the public library income. The level of resources has been generally increased. The number of loans and visits are still rising whereas the number of registered users is slightly dropping. The extent of digitalisation of library materials has been significantly increased. Research limitation:  The average value of performance indicators is presented. Originality/practical implications:  Results can be used for monitoring public library development.